Protective Effect of Microbubble Aeration and Dietary Probiotics BALSS on Survival and Immunity of White Leg Shrimp (Litopenaeus vannamei) Postlarvae against Acute Low Salinity Stress - Shima Bhaskara Ayuningrum; Indah Istiqomah; Rustadi Rustadi; Bambang Triyatmo; Alim Isnansetyo; Wiratni Budhijanto; Deendarlianto Deendarlianto (Jurnal Perikanan Universitas Gadjah Mada, 2020)
Survival rate and immunity of white leg shrimp ((Litopenaeus vannamei) postlarvae against acute salinity stress were evaluated in indoor experimental trials. The research was conducted with 2x2 factorial design with two levels of aeration (microbubble and macro bubble) and two levels of diet (with and without probiotics) resulting four treatments in triplicate: application of microbubble with gut probiotics (MiP), without gut probiotics (MiC), and macro bubble with gut probiotics (MaP) and without probiotics (MaC). White leg shrimps measuring 7.6 g were maintained in the tanks for 60 days and fed five times a day at a dose of 5% biomass. Harvested shrimp were tested for low salinity stress (5 ppt) for 3 hours. Glucose level, total protein, bactericidal activity, natural agglutination, phenoloxidase, respiratory burst, and superoxide dismutase activities in the hemolymph and the shrimp survival rate (SR) were analyzed before and after the stress tests. Although all examined parameters remained the same between groups before the stress test, significant differences were found among them after the stress test. Microbubble aeration obtained stabilization of hemolymph glucose level, best survival rate, bactericidal activity, and agglutination activities. No significant effect was resulted by the dietary probiotic treatments, but the interaction with aeration treatments revealed the importance to compensate shrimp survival rate when microbubble aeration is unavailable.